3D Printed High‐Loading Lithium‐Sulfur Battery Toward Wearable Energy Storage. (22nd January 2020) - Chen, Chenglong; Jiang, Jiangmin; He, Wenjie; Lei, Wu; Hao, Qingli; Zhang, Xiaogang
Abstract: Wearable electronic devices are the new darling of consumer electronics, and energy storage devices are an important part of them. Here, a wearable lithium‐sulfur (Li‐S) bracelet battery using three‐dimensional (3D) printing technology (additive manufacturing) is designed and manufactured for the first time. The bracelet battery can be easily worn to power the wearable device. The "additive" manufacturing characteristic of 3D printing provides excellent controllability of the electrode thickness with much simplified process in a cost‐effective manner. Due to the conductive 3D skeleton providing interpenetrating transmission paths and channels for electrons and ions, the 3D Li‐S battery can provide 505.4 mAh g −1 specific capacity after 500 cycles with an active material loading as high as 10.2 mg cm −1 . The practicality is illustrated by wearing the bracelet battery on the wrist and illuminating the red light‐emitting diode. Therefore, the bracelet battery manufactured by 3D printing technology can address the needs of the wearable power supply. Abstract : A 3D lithium‐sulfur battery bracelet based on direct ink writing and fused deposition 3D printing is manufactured for the first time. The combination of 3D printing technology with battery manufacturing not only brings about this exciting wearable lithium‐sulfur battery bracelet, but also provides new ideas for the design and manufacture of future energy storage devices.